Utilizing technology for diet and exercise change in complex chronic conditions across diverse environments (U-DECIDE): feasibility randomised controlled trial - Riley C. C. Brown; Shelley E. Keating; Dev K. Jegatheesan; Hannah L. Mayr; Amandine Barnett; Marguerite M. Conley; Lindsey Webb; Jaimon T. Kelly; Centaine L. Snoswell; Heidi M. Staudacher; Graeme A. Macdonald; Nicola W. Burton; et al. (BMC, 2024)
Abstract Background Diet and exercise are important components of treatment for complex chronic conditions, however access to allied health support is limited. When available, support is often siloed and fragmented. Digital health incorporating patient choice may help to align health care services with preferences and goals. This study evaluated the implementation of a ubiquitously accessible patient-centred digital health diet and exercise service. Methods U-DECIDE was a single-centre, 26-week randomised controlled trial set in kidney and liver disease clinics in a tertiary hospital in Brisbane, Australia. Participants were adults with a complex chronic condition referred for dietetic consultation with at least one feature of the metabolic syndrome. All participants received a dietary consultation, an activity monitor and usual care. Intervention participants were offered one text message per week and access to additional digital health options (increased text message frequency, nutrition app, exercise app, group-based diet and/or exercise video consultations). The primary outcome of feasibility was determined by safety (study-related serious adverse events: SRSAEs), recruitment (≥ 50% eligible patients), retention (≥ 70%), exposure uptake (≥ 75% of intervention group had greater access to health professional contact than comparator) and video consultation adherence (≥ 80% attendance). Secondary outcomes included process evaluation metrics and clinical outcomes. Results Of 67 participants (intervention n = 33, comparator n = 34), 37 (55%) were men, median (IQR) age was 51 (41-58) years. The most chosen digital health options were the nutrition app (n = 29, 88%) and exercise video consultations (n = 26, 79%). Only one participant chose no additional digital health options. The intervention group had no SRSAEs. The study exceeded targets for recruitment (52%), retention (81%) and exposure uptake (94%). Video consultation adherence was 42%. Engagement across digital health options was inconsistent. Conclusions Digital health options incorporating patient choice were feasible and can be offered to people with complex chronic disease as a service model option. Trial registration Australia and New Zealand Trials Register: Trial Registration Number: ACTRN12620001282976. Registered 27th November 2020.